CONTROL OF A DC MOTOR USING FUZZY LOGIC CONTROL ALGORITHM (Nigerian Journal of Technology, 2017)
ABSTRACTThis study sought to establish the impact of a fuzzy logic controller (FLC) and a Proportional-Integral-Derivative (PID) controller in the control performance of an industrial type DC motor using MATLAB. The fuzzy logic controller was developed on the basis of Mamdani type fuzzy inference system (FIS). The centroid method of defuzzification was also adopted. A choice of seven membership functions was designed for the error and change in error inputs alongside the output, hence a resultant of 49 rules was achieved for the fuzzy controller. Simulations for the PID controller and with the fuzzy controller were obtained at no load and for a selected reference speed of 1200 rpm. The simulations were further repeated for a load torque of 7Nm with the same reference speed. The simulated results were compared. Based on the findings, it was observed that the fuzzy speed controlled DC motors perform better than the PID speed controlled DC motors in terms of its faster settling time, absence of an overshoot and its sensitivity to applied load. Sequel to the foregoing findings, the researchers concluded that fuzzy logic controllers should be readily implemented in our local industries to enhance precision and improve performance in operations involving DC motors.http://dx.doi.org/10.4314/njt.v36i2.35